Faktor-faktor yang Menentukan Loyalitas Pelanggan - Ahmad; Umar Syarif (International Journal Administration, Business & Organization, 2020)
The purpose of this study is to test the determinant factors that affect consumer loyalty. The independent variables used are the concept of product quality, service quality, and price. For this research, 98 consumers are used as samples. The data are gathered through questionnaires and survey methods. The researched data are processed using a mean test and multiple regression. The result of this study shows that product quality, service quality, and price partially affect consumer loyalty. Each research variable partially proves a very strong influence on consumer loyalty. The dominant factor influencing customer loyalty is price.